Multikingdom characterization of gut microbiota in patients with rheumatoid arthritis and rheumatoid arthritis‐associated interstitial lung disease - Xing, Yida; Liu, Yiping; Sha, Shanshan; Zhang, Yue; Dou, Yuemeng; Liu, Changyan; Xu, Mingxi; Zhao, Lin; Wang, Jingdan; Wang, Yan; Ma, Xiaochi; Yan, Qiulong; et al. (Journal of medical virology, 2024)
Rheumatoid arthritis‐associated interstitial lung disease (RA‐ILD) is a serious and common extra‐articular disease manifestation. Patients with RA‐ILD experience reduced bacterial diversity and gut bacteriome alterations. However, the gut mycobiome and virome in these patients have been largely neglected. In this study, we performed whole‐metagenome shotgun sequencing on fecal samples from 30 patients with RA‐ILD, and 30 with RA‐non‐ILD, and 40 matched healthy controls. The gut bacteriome and mycobiome were explored using a reference‐based approach, while the gut virome was profiled based on a nonredundant viral operational taxonomic unit (vOTU) catalog. The results revealed significant alterations in the gut microbiomes of both RA‐ILD and RA‐non‐ILD groups compared with healthy controls. These alterations encompassed changes in the relative abundances of 351 bacterial species, 65 fungal species, and 4,367 vOTUs. Bacteria such as Bifidobacterium longum, Dorea formicigenerans, and Collinsella aerofaciens were enriched in both patient groups. Ruminococcus gnavus (RA‐ILD), Gemmiger formicilis, and Ruminococcus bromii (RA‐non‐ILD) were uniquely enriched. Conversely, Faecalibacterium prausnitzii, Bacteroides spp., and Roseburia inulinivorans showed depletion in both patient groups. Mycobiome analysis revealed depletion of certain fungi, including Saccharomyces cerevisiae and Candida albicans, in patients with RA compared with healthy subjects. Notably, gut virome alterations were characterized by an increase in Siphoviridae and a decrease in Myoviridae, Microviridae, and Autographiviridae in both patient groups. Hence, multikingdom gut microbial signatures showed promise as diagnostic indicators for both RA‐ILD and RA‐non‐ILD. Overall, this study provides comprehensive insights into the fecal virome, bacteriome, and mycobiome landscapes of RA‐ILD and RA‐non‐ILD gut microbiota, thereby offering potential biomarkers for further mechanistic and clinical research.